Enhancing Competitiveness of Indonesian Culinary SMEs: The Role of Entrepreneurial Networks, Entrepreneurial Bricolage, and Frugal Innovation - Alamanda, Dini Turipanam; Anggadwita, Grisna; Profityo, Werda Bagus Profityo Bagus; Kurniati, Dinar Mariam (Faculty of Economic and Business, Universitas Islam Negeri Syarif Hidayatullah, 2024)
Research Originality: This study comprehensively analyzes entrepreneurial networks, bricolage, and frugal innovation within the context of Indonesian culinary SMEs.Research Objectives: This study explores how entrepreneurial networks, entrepreneurial bricolage, and frugal innovation contribute to improving the competitiveness of SMEs in Indonesia's culinary sector.Research Methods: Data analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) with a total of 100 culinary SMEs across various regions of Indonesia.Empirical Results: This study reveals that while entrepreneurial networks do not directly impact competitiveness, they play a crucial role in fostering entrepreneurial bricolage and frugal innovation. These two constructs, in turn, significantly enhance the competitiveness of SMEs.Implications: This research provides insights on how SMEs in emerging economies can harness resourcefulness and innovation to sustain growth and competitiveness.JEL Classification: L14, L26, O31, O32